Fatigue life estimation of a notched component using frequency domain technique and probabilistic linear cumulative damage model. - Pascualinotto Junior, Vagner (2021)
Engineering structures are designed to withstand a variety of in service loading specific to their intended application. Random vibration excitation is observed in most of the structural components in the offshore, aerospace and automotive industries. Likewise, fatigue life estimation for structural components is fundamental for the verification of the design and assurance of the structural integrity throughout service. The linear cumulative damage model (Palmgren-Miners rule) is still largely used for damage assessment, even though, its limitations are well-known. The scatter of fatigue testing data suggests that a probabilistic characterization of the material behavior is needed. In this work, the inherent uncertainties of the fatigue phenomenon as well as the influence of a geometrical discontinuity (notch) are explored in the fatigue life estimation of a structural component subjected to random vibration profiles. The fatigue life estimated using the methodology proposed in this work presented good agreement with testing results using both Lallane and Dirlik frequency domain counting methods. Lallanes method resulted in a 3% more conservative prediction than the average physical testing fatigue life, while Dirliks method, resulted in an 8.4% higher predicted life for the most relevant load case.